Overview of Medication Storage at The Limbong Puskesmas UPT Rongkong District, North Luwu District - Murniati, Murniati; Amiruddin, Achmad; Pojie, Andi Colli (Jurnal Farmasi Sandi Karsa, 2022)
The community health center, also known as the Puskesmas, is a first-level health facility that provides services for public health efforts and individual health efforts prioritizing promotive and preventive without neglecting curative and rehabilitative efforts. The purpose of this study was to find out how the description of drug storage at UPT Puskesmas Limbong, Rongkong District, North Luwu Regency, based on spatial arrangements, how to store drugs, record stock cards, observe drug quality. Spatial planning obtained good results, but some were not appropriate, namely special cabinets for narcotics and psychotropics which were not guaranteed to be safe and did not have locks. The method of storing medicines at the UPT Puskesmas Limbong, Rongkong District, North Luwu Regency based on FIFO and FEFO and the alphabet, obtained good results. Although there are those that do not meet the requirements, namely the special cupboards for narcotics and psychotropics, their safety is not guaranteed and they do not have a key. Stock cards are used to record drug mutations (receipt, dispensing, damaged and expired). Stock card recording has a good category. Observation of drug quality obtained good results. Description of drug storage in the drug warehouse at the UPT Puskesmas Limbong, Rongkong District, North Luwu Regency in 2022 is in the good category with a percentage value of 92.5% consisting of 80% spatial arrangement, 90% drug storage method, 100% stock card recording and drug quality observation by 100%.